PENGARUH KERAGAMAN PRODUK, FASILITAS DAN E-WOM TERHADAP KEPUASAN KONSUMEN PADA CAFE FORTUNA DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Sari, Putri Ayu Purnama; Wahyuni, Ika; Ediyanto, Ediyanto (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
In the current era of Society 5.0, more and more unique culinary places have emerged as destinations to enjoy food and drinks known as cafes. The purpose of this study was to analyze the role of product diversity, facilities, and E-WOM in influencing consumer satisfaction and purchasing decisions at Cafe Fortuna. The population in this study were Cafe Fortuna consumers. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Last Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that product diversity has a significant positive effect on purchasing decisions, facilities have a negative but insignificant effect on purchasing decisions, E-Wom has a positive but insignificant effect on purchasing decisions, product diversity has a positive but significant effect on customer satisfaction, facilities have a negative but insignificant effect on customer satisfaction, facilities have a positive effect on customer satisfaction, purchasing decisions have a significant positive effect on customer satisfaction through purchasing decisions, product diversity has a significant positive effect on customer satisfaction through purchasing decisions, facilities have a negative but insignificant effect on customer satisfaction through purchasing decisions, E-Wom has a positive but insignificant effect on customer satisfaction through purchasing decisions.